Selenium-containing analogues of WC-9 are extremely potent inhibitors of Trypanosoma cruzi proliferation. Issue 24 (15th December 2017) - Chao, María N.; Storey, Melissa; Li, Catherine; Rodríguez, Maricel G.; Di Salvo, Florencia; Szajnman, Sergio H.; Moreno, Silvia N.J.; Docampo, Roberto; Rodriguez, Juan B.
Graphical abstract: Abstract: The obligate intracellular parasite, Trypanosoma cruzi is the etiologic agent of Chagas disease or American trypanosomiasis, which is the most prevalent parasitic disease in the Americas. The present chemotherapy to control this illness is still deficient particularly in the chronic stage of the disease. The ergosterol biosynthesis pathway has received much attention as a molecular target for the development of new drugs for Chagas disease. Especially, inhibitors of the enzymatic activity of squalene synthase were shown to be effective compounds on T. cruzi proliferation in in vitro assays. In the present study we designed, synthesized and evaluated the effect of a number of isosteric analogues ofWC-9 (4-phenoxyphenoxyethyl thiocyanate), a known squalene synthase inhibitor, on T. cruzi growth in tissue culture cells. The selenium-containing derivatives turned out to be extremely potent inhibitors of T. cruzi growth. Certainly, 3-phenoxyphenoxyethyl, 4-phenoxyphenoxyethyl, 4-(3-fluorophenoxy)phenoxyethyl, 3-(3-fluorophenoxy)phenoxyethyl selenocyanates and (±)-5-phenoxy-2-(selenocyanatomethyl)-2, 3-dihydrobenzofuran arose as relevant members of this family of compounds, which exhibited effective ED50 values of 0.084 µM, 0.11 µM, 0.083,  µM, 0.085, and 0.075 µM, respectively. The results indicate that compounds bearing the selenocyanate moiety are at least two orders of magnitude more potent than the corresponding skeleton counterpart bearing the thiocyanate group. Surprisingly, these compounds exhibited excellent selectively index values ranging from 900 to 1800 making these molecules promising candidates as antiparasitic agents.